Transcendence, Spirituality, Practices, Immanence: A Conversation with Antonio Negri. Issue 3 (1st October 2016) - Revel, Judith
Abstract : Antonio Negri answers three questions posed by Judith Revel: on the necessary transcendence of spirituality, or on its potential redefinition as immanence of practices; on Francis of Assisi between mysticism and poverty; and on the possible interpretation of Spinoza as an ontology of immanence entirely built against all metaphysics of transcendence. Negri replies by retracing his own political and philosophical past and trying to reaffirm what he thinks must be defined as the "smile" of revolt.